Implementasi Buku Kontrol Sholat sebagai Instrumen Pembentukan Disiplin Religius Siswa: Studi Kualitatif di SMP Muhammadiyah 1 Makassar - Sandi Pratama (Lembaga Yasin AlSys, 2026)
Religious discipline is one of the core objectives of Islamic education at the junior secondary level; however, limited school time to facilitate obligatory prayers and weak supervision of worship outside school create a gap between students’ religious knowledge and their actual worship practices. This study aimed to examine the implementation of a prayer monitoring book as an instrument for fostering students’ religious discipline, to analyze teachers’, students’, and parents’ perceptions of its use, and to identify the forms of religious discipline and the obstacles encountered in its implementation at SMP Muhammadiyah 1 Makassar. A qualitative case study approach was employed, with participants comprising the principal, Al-Islam Kemuhammadiyahan teachers, homeroom teachers, Grade VII–IX students, and parents. Data were collected through observation, in-depth interviews, and documentation, and analyzed using the Miles and Huberman interactive model. The findings indicate that the prayer monitoring book is implemented systematically through a mechanism of completion and verification by parents and regular inspection by teachers, thereby contributing to increased punctuality in performing prayers, enhanced personal responsibility among students, and greater awareness of worship outside the school environment. Nevertheless, technical, psychological, and coordination-related constraints were identified that affect the consistency of its implementation. It can be concluded that the prayer monitoring book is effective as an instrument for nurturing religious discipline when supported by consistent supervision and sustained collaboration between school and parents, with important implications for the development of more humanistic and reflective worship monitoring instruments in the context of Islamic education.